2020
DOI: 10.3390/su12052053
|View full text |Cite
|
Sign up to set email alerts
|

Land Use, Livestock, Quantity Governance, and Economic Instruments—Sustainability Beyond Big Livestock Herds and Fossil Fuels

Abstract: The production of animal food products is (besides fossil fuels) one of the most important noxae with regard to many of the environmental problems, such as climate change, biodiversity loss or globally disrupted nutrient cycles. This paper provides a qualitative governance analysis of which regulatory options there are to align livestock farming with the legally binding environmental objectives, in particular the Paris Agreement and the Convention on Biological Diversity. Two innovative governance approaches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 75 publications
0
50
0
2
Order By: Relevance
“…To this end, a multi-method governance analysis (or steering analysis) is applied. The analysis evaluates the impact of real or proposed governance instruments towards a given normative objective by taking findings of research on human behaviour and typical governance problems into account [11][12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…To this end, a multi-method governance analysis (or steering analysis) is applied. The analysis evaluates the impact of real or proposed governance instruments towards a given normative objective by taking findings of research on human behaviour and typical governance problems into account [11][12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…(1) Reduction in GHG emissions, which is mainly achieved by phasing out fossil fuels and globally minimizing livestock farming [5][6][7]. (2) Compensation of residual emissions by enhancing natural sink capacities in the land-use sector, specifically through forest management, rewetting of wetlands, and agricultural management [8][9][10][11].…”
Section: Introduction and Scope Of The Papermentioning
confidence: 99%
“…Forest restoration and sustainable forest management (under certain conditions that avoid trade-offs also afforestation and reforestation) [24,25,[157][158][159], enhanced carbon sequestration in soils, stimulated by altered agricultural practices, i.e., agroforestry catch cropping, etc. [144,[160][161][162], and rewetting peatlands [163] are potential measures to enhance these capacities (on policy instruments for the land-use sector see in detail [5,6,9,144]). Even if certain trade-offs must also be taken into account, end-of-pipe solutions such as large-scale geoengineering measures do not solve other environmental problems, such as the progressing ecosystem degradation and acidification, which are also caused directly or indirectly by using fossil fuels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies would have to be supplemented by the above-mentioned overarching instruments, which reduce the intensification pressure in agriculture firstly in Europe but due to highly globalized feed and food markets also globally. Elsewhere, it has been shown that a cap-and-trade approach for fossil fuels with a cap of zero in about two decades and a cap-and-trade approach for livestock husbandry or an obligation to link livestock farming to the agricultural area on the farm area would be, combined with an increase in area-related taxes, the most effective instruments to reduce the land-use pressure (more precisely [9,24,32,143,144]). The fact that such approaches have to be combined with border adjustments in order to prevent shifting effects outside the EU has also been discussed elsewhere.…”
Section: Discussion and Concluding Remarks: Possible Governance Problmentioning
confidence: 99%